2023
DOI: 10.3389/fimmu.2023.1148591
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the causal effect between gut microbiota, DHA, and urate metabolism: A large-scale bidirectional Mendelian randomization

Abstract: ObjectivesOur aim was to investigate the interactive causal effects between gut microbiota and host urate metabolism and explore the underlying mechanism using genetic methods.MethodsWe extracted summary statistics from the abundance of 211 microbiota taxa from the MiBioGen (N =18,340), 205 microbiota metabolism pathways from the Dutch Microbiome Project (N =7738), gout from the Global Biobank Meta-analysis Initiative (N =1,448,128), urate from CKDGen (N =288,649), and replication datasets from the Global Urat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Due to differences in data, such as the inclusion of different participants, the other researchers have also found that Escherichia Shigella, Lachnospiraceae NC2004 group, Family XIII AD3011 group, Coprococcus 3, Bifidobacteriales order and Bifidobacteriaceae family are closely related to gout. 67,68 These findings could be mutually complementary with our results.…”
Section: Discussionsupporting
confidence: 90%
“…Due to differences in data, such as the inclusion of different participants, the other researchers have also found that Escherichia Shigella, Lachnospiraceae NC2004 group, Family XIII AD3011 group, Coprococcus 3, Bifidobacteriales order and Bifidobacteriaceae family are closely related to gout. 67,68 These findings could be mutually complementary with our results.…”
Section: Discussionsupporting
confidence: 90%
“…The process of selecting instrumental variables (IVs) for exposure in MR adhered to certain guidelines [ 40 ]. For every microbiota taxon and pathway, variants that exhibited a genome-wide significance level of p < 1 × 10 −5 and effect allele frequency (EAF) of >0.01 were included [ 41 ]. These genetic variants were subjected to a clumping process using a linkage disequilibrium threshold of r 2 < 0.001 by leveraging the 1000 Genomes European reference panel.…”
Section: Methodsmentioning
confidence: 99%
“…Heterogeneity was estimated by Cochran’s Q statistic, and the results with the P-value < 0.05 were removed due to their heterogeneity. Furthermore, we conduct The Mendelian Randomization Pleiotropy Residual Sum and Outlier(MR-PRESSO) tests to assess horizontal pleiotropy [ 35 ], and the MR Steiger test to ensure the right causal direction from exposure to outcome [ 36 ]. The Benjamini‒Hochberg method was used to evaluate the false discovery rate(FDR) and provided corrected FDR Q-value [ 37 ], which methods have been widely performed in this field.…”
Section: Methodsmentioning
confidence: 99%